2005
DOI: 10.1902/jop.2005.76.5.696
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan‐1 Expression During the Formation of Junctional Epithelium

Abstract: Results of syndecan-1 mRNA and protein expression patterns suggested that this proteoglycan might be an important molecule during the formation of JE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
24
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 35 publications
4
24
0
1
Order By: Relevance
“…In mesenchymal cells the syndecan-1 level is usually low, but it is elevated transiently during embryonal morphogenesis (6872) concomitant with a loss of syndecan-1 in the adjacent epithelium. Given this low syndecan-1 level in mesenchymal tumors, the expression, and function of syndecan-1 is far less studied than in carcinomas.…”
Section: Syndecan-1 In Mesenchymal Tumorsmentioning
confidence: 99%
“…In mesenchymal cells the syndecan-1 level is usually low, but it is elevated transiently during embryonal morphogenesis (6872) concomitant with a loss of syndecan-1 in the adjacent epithelium. Given this low syndecan-1 level in mesenchymal tumors, the expression, and function of syndecan-1 is far less studied than in carcinomas.…”
Section: Syndecan-1 In Mesenchymal Tumorsmentioning
confidence: 99%
“…In wounds that are remodeling over a period of weeks, perlecan levels in the subepithelial connective tissues appear to remain relatively high (SundarRaj et al, 1998). Perlecan has been demonstrated in periodontal ligament fibroblasts (Larjava et al, 1992), and its heparan-sulfatedecorated cell-surface homologues, the syndecans 1-4, have been detected in association with the formation of junctional epithelium (Dias et al, 2005). Perlecan has also been detected in the basement membranes of human tissues, including the pituitary gland, skin, breast, thymus, prostate, colon, liver, pancreas, spleen, heart, and lung.…”
Section: Perlecan a Heparan Sulfate Proteoglycanmentioning
confidence: 99%
“…It is involved in epithelial–mesenchymal interactions regulating growth, compartmentalization, and determination of dental mesenchymal cell lineage during early tooth development 2‐5 . Studies related to syndecan‐1 expression of postnatal tooth development have focused on epithelial cells, 6‐9 the periodontium, 10 and the wound‐healing process 11,12 . We recently demonstrated that syndecan‐1 is an important molecule during the formation of junctional epithelium 7 .…”
mentioning
confidence: 99%
“…Studies related to syndecan‐1 expression of postnatal tooth development have focused on epithelial cells, 6‐9 the periodontium, 10 and the wound‐healing process 11,12 . We recently demonstrated that syndecan‐1 is an important molecule during the formation of junctional epithelium 7 . These studies indicated that syndecan‐1 expression is important for cell biology and for clinical applications in the field of dentistry.…”
mentioning
confidence: 99%
See 1 more Smart Citation